Desenvolvimento de Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae) em Brassicaceae ao longo de gerações - Dibelli, Wanderlei [UNESP] (2014)
Species of Brassicaceae family are part of the global food base. Nutritional characteristics of brassics show high levels of vitamins, fiber, minerals, phenols, flavonoids, hydroxycinnamic acid, soluble sugars, fatty acids and carotenoids, and secondary substances such as glucosinolates that are currently recognized by the antioxidant and anti-carcinogenic effects. The diamondback moth, Plutella xylostella, is one of the main limiting factors of this crop in the world, due to the serious damage that cause to plants, depreciating the product and causing serious reductions in the field production. The knowledge of the biology of this insect in different cultivars is important so that you can determine those less favorable to the pest development and reproduce. In this context, the objective of this study was to evaluate the influence of the larvae food substrate (Brassicaceae’s varieties) in the P. xylostella development over 18 generations. Insects were reared on 3 comercial varieties/cultivars of importance to the northeastern of Sao Paulo State: Brassica oleracea var. acephala - kale Manteiga hibrida HS-20, Brassica oleracea var. italica - broccoli Piracicaba and Brassica oleracea var. capitata - cabbage Bob Cat. Every 3 generations the biological aspects of P. xylostella were evaluated in laboratory trials. The biological parameters evaluated were: leaf consumption, larval period, larval viability, pupal period, pupal viability, pupal weight, sex ratio, number of eggs per female, egg fertility, and longevity of males and females. The results were analysed comparing generations and cultivars. The biological parameters of P. xylostella showed that cabbage cultivar was less consumed and the larval period was longer while the pupal period was shorter. However, the low initial performance of this cultivar was being improved over the generations, matching the others in the latest generations ...